Eye Movements as Indicators of Vestibular Dysfunction. (August 2015) - Menshikova, Galina Ya.; Kovalev, Artem I.; Klimova, Oxana A.; Chernorizov, Alexander M.
Virtual reality technologies are in wide use in sport psychology. An advantage of this kind of technology is the possibility to assess sportspeople's readiness to perform complex movements. This study is aimed at developing a method for the evaluation of vestibular function disturbances in young skaters. Such disturbances may occur while skaters are performing rotation movements. To achieve this goal, we induced a vection illusion, accompanied by virtual environment rotation in a CAVE virtual reality system. Vestibular disturbances were tested for two groups—professional skaters and people who had very little or no skating experience. The quantitative evaluation of vestibular dysfunction was based on eye movement characteristics, which were recorded in subjects experiencing a vection illusion.